Mengungkap Hubungan Antara Engagement Akademik dengan Burnout Akademik Pada Mahasiswa di Perguruan Tinggi Islam - Permata Sari; Moh Alwi Hasan; Mohamad Awal Lakadjo; Agung Prasetyo (Indonesian Journal of Counseling and Development, 2025)
Burnout among university students, characterized by emotional exhaustion, cynicism, and reduced efficacy, has increased following intensified academic demands, making an investigation into protective factors urgent. This study examined the relationship between academic engagement and academic burnout among students at UIN Raden Intan Lampung. Using a quantitative correlational design, data were collected in 2024–2025 via self-administered questionnaires from 123 students selected by simple random sampling. Academic engagement was measured with a researcher-developed 32-item Likert scale covering emotional, cognitive, and behavioral dimensions; academic burnout was assessed with a 36-item scale based on Maslach & Leiter's three dimensions. Instrument validity and reliability were confirmed (Cronbach's α = 0.905 for engagement; α = 0.877 for burnout). Descriptive analyses, assumption tests (Kolmogorov–Smirnov; Levene's), and Pearson correlation (SPSS v25) were employed. Results showed moderate mean scores for engagement (M = 61.37, SD = 14.70) and burnout (M = 60.06, SD = 12.60), and a strong, significant negative correlation between engagement and burnout (r = −0.918, p < 0.001), indicating higher engagement associates with lower burnout. The findings support interventions that strengthen academic engagement through mentoring, active learning, time-management training, and social/spiritual supports to mitigate student burnout. Practical implications include university policy changes and the expansion of counseling and student support services nationwide implementation